2007
DOI: 10.1007/s11273-007-9059-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a citizen monitoring protocol to assess the structure and function of natural and stabilized fringing salt marshes in North Carolina

Abstract: Narrow fringing salt marshes dominated by Spartina alterniflora occur naturally along estuarine shorelines and provide many of the same ecological functions as more extensive marshes. These fringing salt marshes are sometimes incorporated into shoreline stabilization efforts. We obtained data on elevation, salinity, sediment characteristics, vegetation and fish utilization at three study sites containing both natural fringing marshes and nearby restored marshes located landward of a stone sill constructed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 46 publications
(70 reference statements)
2
79
0
Order By: Relevance
“…While the use of citizen scientists is a relatively recent phenomenon, citizens are increasingly being included in conservation and restoration planning (Currin et al 2008;Oscarson and Calhoun 2007) and have been found to be effective assistants to local land managers (Sharpe and Conrad 2006). If a standard protocol is used (e.g., Christmas Bird Count), a diverse public can be used as a local resource that is capable of collecting data on both wetland structure and function (Currin et al 2008).…”
Section: Long-term Citizen-based Monitoring Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of citizen scientists is a relatively recent phenomenon, citizens are increasingly being included in conservation and restoration planning (Currin et al 2008;Oscarson and Calhoun 2007) and have been found to be effective assistants to local land managers (Sharpe and Conrad 2006). If a standard protocol is used (e.g., Christmas Bird Count), a diverse public can be used as a local resource that is capable of collecting data on both wetland structure and function (Currin et al 2008).…”
Section: Long-term Citizen-based Monitoring Schemesmentioning
confidence: 99%
“…If a standard protocol is used (e.g., Christmas Bird Count), a diverse public can be used as a local resource that is capable of collecting data on both wetland structure and function (Currin et al 2008). By utilizing citizen participation, not only are costs lowered compared to traditional data collection methods, but local stewardship is also promoted, with local communities benefiting directly from the educational value of participation (Hudson 2001).…”
Section: Long-term Citizen-based Monitoring Schemesmentioning
confidence: 99%
“…There is some evidence that current nitrate concentrations exceed levels observed several decades ago (Micheli et al 2008), suggesting some deterioration in water quality, but the lack of longterm records leaves this trend inconclusive. In response to rising sea levels, rock sills have been installed in Bogue Sound marshes since 1998 (Currin et al 2008).…”
Section: Study Systemmentioning
confidence: 99%
“…The area behind the sill is then backfilled with sediment and marsh cordgrass (Spartina alterniflora) is planted. The extent to which such restored and stabilized marshes achieve ecosystem function of natural marshes is beginning to be evaluated (Currin et al 2008). Some ecosystem properties such as marsh grass density and fish abundance return fairly quickly to levels similar to natural marshes, but accretion rates and other biogeochemical processes such as soil nitrogen storage may take longer (Piehler et al 1998;Currin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation